2016 IEEE Globecom Workshops (GC Wkshps) 2016
DOI: 10.1109/glocomw.2016.7849056
|View full text |Cite
|
Sign up to set email alerts
|

Target Tracking with a Flexible UAV Cluster Array

Abstract: Abstract-Unmanned aerial vehicle (UAV) cluster applications, for tasks such as target localisation and tracking, are required to collect and utilise the data received on "flexible" sensor arrays, where the sensors, i.e. UAVs in this scenario, have time-variant positions. In this paper, using a parametric channel model, a UAV cluster mobility model and a kinematic model of the targets, an extended Kalman based state space model is proposed that tracks the unknown UAV positions and target parameters snapshot by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…These mobile platforms perform online coded capture and offline storage and processing such as image correction and matching [262] and other methods in the edge server. As a different example, in the applications of surveillance, one needs to conduct real-time object detection and tracking [263], which can be executed on the edge server and send specific action instructions back to the mobile platform, such as adjusting the speed according to the deviation from the reference [264], or the position of other platforms and objects [265]. Such tasks demand low latency, but are not bandwidth starving.…”
Section: ) Single Mobile Platformmentioning
confidence: 99%
“…These mobile platforms perform online coded capture and offline storage and processing such as image correction and matching [262] and other methods in the edge server. As a different example, in the applications of surveillance, one needs to conduct real-time object detection and tracking [263], which can be executed on the edge server and send specific action instructions back to the mobile platform, such as adjusting the speed according to the deviation from the reference [264], or the position of other platforms and objects [265]. Such tasks demand low latency, but are not bandwidth starving.…”
Section: ) Single Mobile Platformmentioning
confidence: 99%
“…Among these, UAVs are rapidly gaining popularity for research and applications in cooperative robotics, due to the availability of reliable, stable, and cost-effective devices which are also able to carry a variety of sensors. Recent research concerning multirobots target tracking based on UAV clusters can be found in [3], in which cooperative control of fixed-wings UAVs is addressed for the tracking of ground mobile targets emitting radio-frequency signals; in [4], the path planning strategy for video-based tracking of ground targets is especially aimed at maximizing the visibility of the target in an urban area setting; thus, when ground obstacles of different shapes and sizes may cause occlusion; in [5], a study on the localization and tracking of a generic target through a cluster of UAVs with acoustic sensors is illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…The "flexible array" is defined as an antenna array with time varying geometry, i.e. each of the array elements move independently and this paper is an extension of [30] where a flexible array formed by a swarm of unmanned aerial vehicles (UAVs) is presented. If the array geometry is flexible, i.e.…”
mentioning
confidence: 99%
“…This paper is concerned with tracking the DOA of multiple sources in non-stationary wireless communications using both rigid arrays and flexible arrays. In addition to [30] in the current literature, to the best of our knowledge, there are only two papers [37], [38] that deal with the tracking using time-varying arrays. [37] is concerned with tracking stationary sources using an array of hydrophones.…”
mentioning
confidence: 99%
See 1 more Smart Citation